Maladaptive daydreaming in Individuals with Disorganized Attachment Style: A Case Report - Anandarani VS, Anandarani VS; Roneena, AJ (Journal of Research in Social Science and Humanities, 2023)
Maladaptive daydreaming is an unrecognized clinical syndrome that encompasses an unhealthy use of fantasy. Hereunder we report on the case of a 19-year-old South Asian girl with a disorganized attachment style who adopted Maladaptive daydreaming as a coping mechanism. The patient sought fantastical proximity with a famous personality to compensate for the lack of an inclination to pursue a healthy romantic relationship in real life. Deteriorating relationships with friends and family, social anxiety, and cascades of unimpressive academic performances prompted the patient to browse for answers on the internet. She discovered the 16-item Maladaptive Daydreaming scale (MDS-16) on which she scored above the cut-off score. Subsequent psychotherapy sessions wherein she was encouraged to journal her MD breaks and practice mindfulness meditation led to the patient reporting significant improvements in her professional and personal life and better control over her yearnings to daydream. We report this case to raise awareness for a disorder that shows semblances of behavioral addiction and risks being misdiagnosed or even undetected in some clinical contexts.